Symptoms and signs of progressive hydrocephalus. Issue 1 (January 1989) - Kirkpatrick, M; Engleman, H; Minns, R A
Abstract : The clinical features of 107 cases of children with hydrocephalus and measured raised intraventricular pressure were analysed retrospectively. Fifty one children had recently been diagnosed as having hydrocephalus, and the remainder had had shunts injected to direct the cerebrospinal fluid. The most common symptoms in the group were vomiting, behavioural changes, drowsiness, and headaches. The most common clinical signs were inappropriately increasing occipitofrontal head circumferences, tense anterior fontanelles, splayed sutures, and distension of the scalp veins. Half the infantile cases of hydrocephalus were without symptoms, and a quarter of the cases with cerebrospinal fluid shunts and measured raised intraventricular pressure were without signs. There were no fewer than 33 different clinical signs including several unusual ones, such as macular rash and sweating. We believe that the presentation of hydrocephalus with raised intraventricular pressure is sufficiently variable, unusual, or even absent to justify the direct measurement of intracranial pressure.